Pesticide exposure and cholinesterase levels of crop farmers in Tanah Karo District - Rio Ferdi Yuandra; Taufik Ashar; Rahayu Lubis (Berita Kedokteran Masyarakat (BKM), 2020)
Background. Majority of population in Tanah Karo District, Indonesia are farmers (88.54%), which is always use pesticides to their planting. The use of pesticides with high intensity and continuously will cause a negative impact on health.Purpose. The purpose of this research was to analyze the relationship between pesticide exposure, including the length of work, length of spraying, spraying techniques and Personal Protection Equipment (PPE) with farmers' cholinesterase levels.Method. This research was an observational analytic with a cross sectional approach. Samples were 40 farmers. Data collection through questionnaires and health checks. Data analysis was performed using univariate and bivariate with chi-square test.Result. The result showed that from 40 farmers, 13 farmers had below normal cholinesterase levels, there was relationship between the length of spraying, spraying techniques, and the use of PPE with cholinesterase levels with p<0,05 and there was no relationship between length of work with  level of cholinesterase p>0,05.Conclusion. Farmers who have long been exposed to pesticides can reduce levels of cholinesterase, especially if they don't pay attention to spraying techniques and use PPE, it can cause poisoning. It is recommended to the Department of Agriculture Karo District to monitor and supervise the use of pesticides on farmers, and for farmers to pay attention to the use of PPE, spraying techniques, and monitor their health status regularly at the health center.